Analisis Pengukuran Kerja untuk Menentukan Waktu Baku dalam Peningkatan Produktivitas Produksi Tube Underfloor di PT. UVW Indonesia - Utomo, Nugroho Priyo; Febriansyah, Raja Dafa; Pramudianto, Muhammad Agus Kurniawan; Setiawan, Muhamad Budi; Iqbal, Muhamad; Irwati, Dwi (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze work measurement using the time study method to determine cycle time, normal time, and standard time on the Tube Underfloor production line at PT. UVW Indonesia. The research was conducted on the Tube Assembling Line 11, consisting of four workstations: Brazing, Bending, Assembling, and Quality Inspection. Data were collected using a stopwatch method with 30 measurements per station. The data were tested for uniformity and adequacy, followed by the calculation of normal time using the Westinghouse adjustment method and a 12% allowance factor. The results showed that the highest standard time occurred during the assembling process (74.1 seconds), and the lowest during quality inspection (40.0 seconds). The standard output was determined to be 49 units per hour. These findings indicate that a systematic work measurement method can help the company set realistic work standards and enhance overall efficiency and productivity.